Measurement and Prediction of Fuel Oxygenates Mixtures Excess Thermophysical Properties - A Review - T. K., Thanusha; R., Ramesh; N. A. F. A., Samad; Mohd Yusri, Mohd Yunus; K., Ramesh (2015)
Excess thermophysical properties are important in understanding the molecular interaction between unlike molecules. The excess properties data are very important for process design and separation, especially in chemical industry. The excess thermophysical properties reviewed are excess molar volume, excess molar enthalpy and viscosity. In this review, particular interest is taken on binary mixtures of fuel oxygenates which are methyl tert-butyl ether (MTBE), ethyl tert-butyl ether (ETBE), tert-amyl methyl ether (TAME) with lower alcohols. This review will enable researchers to know what are the mixtures studied and where future work is required.